Board of director gender and corporate tax aggressiveness: An empirical analysis - Lanis, R.; Richardson, G.; Taylor, Grantley (Springer Netherlands, 2015)
This study examines the impact of board of director gender diversity on corporate tax aggressiveness. Based on a sample of 418 U.S. firms covering the 2006–2009 period (1672 firm-year observations), our ordinary least squares regression results show a negative and statistically significant association between female representation on the board and tax aggressiveness after controlling for endogeneity. Our results are consistent across several measures of tax aggressiveness and additional robustness checks.